2021
DOI: 10.3390/jcm10102207
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers to Guide the Timing of Surgery: Neutrophil and Monocyte L-Selectin Predict Postoperative Sepsis in Orthopaedic Trauma Patients

Abstract: Deciding whether to delay non-lifesaving orthopaedic trauma surgery to prevent multiple organ failure (MOF) or sepsis is frequently disputed and largely based on expert opinion. We hypothesise that neutrophils and monocytes differentially express activation markers prior to patients developing these complications. Peripheral blood from 20 healthy controls and 162 patients requiring major orthopaedic intervention was collected perioperatively. Neutrophil and monocyte L-selectin, CD64, CD11, CD18, and CXCR1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Considering the novelty of LYZ as an indicator of sepsis recovery and clinical benefits of CRRT, the underlying mechanisms of LYZ involved in roles of CRRT in pediatric sepsis is worth of more attention in the future. In addition, several studies have shown that SELL [15] and SERPINA3 [30] are also associated with sepsis, but it was not confirmed in our present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Considering the novelty of LYZ as an indicator of sepsis recovery and clinical benefits of CRRT, the underlying mechanisms of LYZ involved in roles of CRRT in pediatric sepsis is worth of more attention in the future. In addition, several studies have shown that SELL [15] and SERPINA3 [30] are also associated with sepsis, but it was not confirmed in our present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous multicenter study indicated that the level of IL-6 was decreased in the CRRT group compared with the non-CRRT group, and CRRT decreases hospital mortality rate in pediatric severe sepsis, especially in patients with acute respiratory distress syndrome (ARDS) [14]. Consistently, a recent study showed that levels of C-reactive protein (CRP), TNF-α, and IL-6 decreased significantly after CRRT in patients with sepsis-induced acute kidney injury (AKI) [15]. CRRT as an extracorporeal life support could disturb homeostasis and affect the process of sepsis.…”
Section: Introductionmentioning
confidence: 89%
“…However, association with subsequent sepsis occurrence was not an endpoint in the latter study. In a more recent study aiming at guiding the optimal timing of non-lifesaving orthopedic surgery for trauma, authors hypothesized that neutrophils and monocytes express activation markers prior to sepsis development [49]. They found that in the perioperative period, elevated monocyte L-selectin (AUC 0.76 [95%CI 0.63-0.89] was a signi cant predictor of sepsis, thereby precluding urgent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are the first innate immune cells against pathogens due to their array of microbicidal activities ( 60 , 61 ). Clinically, the drop in circulating neutrophils is positively correlated with the occurrence of MOF ( 62 , 63 ). FS-MSCs have an immunomodulatory action through paracrine activity by secreting anti-inflammatory cytokines and growth factors ( 64 ).…”
Section: New Insights Into Hs Therapeutics With Innate Immune Regulationmentioning
confidence: 99%